Percalços imagéticos às avessas do alfabetismo: a percepção da paisagem do centro de São Paulo - Gustin, Jairo Aldemar Bastidas [UNESP] (2013)
This research investigates the morphological principles that rule topoceptive expectations of semi-illiterates pedestrian in an urban landscape. The experimental study, scope qualitative was determine by interactional approach and some practical tools (representative and oral). Established a spatial area including the main spatiality of the historic triangle of the São Paulo’s center and some adjacent areas inhabited by the five members of the sample. It is believed that the excessive disposition and purposeful of heterogeneous typological features, resulting from globalization, misrepresents the apprehension of existing sets. Thus, the urban landscape explicit cadre perceptive complex fragmented and disjointed that impact on transitory legibility. Nevertheless, interviewee admit attend this spatiality, is enigmatic evidence how the compilation of visual information is block by some instance (objects and / or circumstances). Roughly sketched up an explicative approach associated to the power of visual pregnant of some architectural elements, this is, visual landmarks of Lynch, whose stronger bond converges with some ancestral idyllic sets of the center. However, it was also proved the imperious tendency of respondents choices of functional pragmatic of the numeric symbols for their survival. The outlined scenario corroborates the indispensable role of the contextual joints resulting from sociocultural dimensions that enable the decline or dissipation of some specific barriers. This fact reveals the existence of intrinsic patterns of functioning and decoding of the urban landscape, considered to be unique, but they have value analogous to dominate by subject circumscribed to egis literate. Promulgates the importance of building singular mental maps individuals linked to their everyday experience and at the same time, the repel of layers of imagery cognitive processes that raise and move dynamically, at times, for the opportunity to...